Integrated framework for early warning system in UAE. Issue 4 (12th September 2016) - Alhmoudi, Abdulla Ali; Aziz, Zeeshan
Abstract : Purpose: The impacts and costs of natural disasters on people, properties and environment are often severe when these occur on a large scale and with no warning system in place. The lack of deployment of an early warning system (EWS), low risk and hazard knowledge and impact of natural hazard experienced by some communities in the UAE have emphasised the need for more effective EWSs. This work focuses on developing an integrated framework for EWSs for communities prone to the impact of natural hazards to reduce their vulnerability and improve emergency management arrangements in the UAE. Design/methodology/approach: The essential elements of effective EWS were identified through literature review to develop an integrated framework for EWS. Semi-structured interviews and questionnaires were also used to identify and confirm hindering factors to deployment of effective EWSs in Abu Dhabi and Fujairah Emirates, while areas that require further development were also identified through this means. Findings: The outcome of this research revealed that the warning for natural hazards in the UAE lacked the required elements for effective EWS, whereas the elements which are present are insufficient to mitigate the impacts of natural hazards. The information in this work emphasises the need to improve two elements, and to develop the other two essential elements of EWS in the UAE. Originality/value: The outcome of this research revealed that the warning for natural hazards in the UAE lacked the required elements for effective EWS, whereas the elements which are present are insufficient to mitigate the impacts of natural hazards. The information in this work emphasises the need to improve two elements and to develop the other two essential elements of EWS in the UAE.